Using meta-differential evolution to enhance a calculation of a continuous blood glucose level. Issue 133 (September 2016) - Koutny, Tomas
Highlights: We describe our model of blood glucose level calculation at its present state of the art. We extract data from an independent study funded by the National Institutes of Health. We test our model with the extracted data, using six testing scenarios to show robustness of our model. Researchers may test our model with their data athttps://diabetes.zcu.cz Abstract: We developed a new model of glucose dynamics. The model calculates blood glucose level as a function of transcapillary glucose transport. In previous studies, we validated the model with animal experiments. We used analytical method to determine model parameters. In this study, we validate the model with subjects with type 1 diabetes. In addition, we combine the analytic method with meta-differential evolution. To validate the model with human patients, we obtained a data set of type 1 diabetes study that was coordinated by Jaeb Center for Health Research. We calculated a continuous blood glucose level from continuously measured interstitial fluid glucose level. We used 6 different scenarios to ensure robust validation of the calculation. Over 96% of calculated blood glucose levels fit A+B zones of the Clarke Error Grid. No data set required any correction of model parameters during the time course of measuring. We successfully verified the possibility of calculating a continuous blood glucose level of subjects with type 1 diabetes. This study signals a successful transition of our research from an animal experiment to a human patient. Researchers can test our model with their data on-line athttps://diabetes.zcu.cz .